Sabotage-tolerance and trust management in desktop grid computing - Domingues, Patrício (2007)
The success of grid computing in open environments like the Internet is highly dependent on the adoption of mechanisms to detect failures and malicious sabotage attempts. It is also required to maintain a trust management system that permits one to distinguish the trustable from the non-trustable participants in a global computation. Without these mechanisms, users with data-critical applications will never rely on desktop grids, and will rather prefer to support higher costs to run their computations in closed and secure computing systems.